Juridical Analysis Of Batam's Authority Of Bp On The Issuance Of Land Management Rights To New Rights Holders In Order To Realize Legal Certainty (Research Study At Batam Business Agency) - Sang Darma Pusa; Darwis Anatami; Ramlan Ramlan; Erniyanti Erniyanti; Soerya Respationo (LITERACY : International Scientific Journals of Social, Education, Humanities, 2023)
The purpose of the study is to determine the legal regulation of the authority of the Batam Concession Agency (BP) on the issuance of land management rights for new rights holders, to determine the implementation of the authority of the Batam Concession Agency (BP) on the issuance of land management rights for new rights holders in order to realize legal certainty, to find out the constraint factors and solutions from the implementation of the authority of the Batam Concession Agency (BP) on the issuance of land management rights for new rights holders for the sake of Realizing Legal Certainty. This thesis research method is normative juridical (legal research) through literature study with an empirical juridical approach (sociological juridical) through field studies aimed at obtaining legal knowledge empirically. The results showed that according to legal arrangements, the Batam Concession Agency (BP) has special authority in terms of issuing land management rights in the Batam area. It shows Batam's strategic position and importance in the country's economic and investment map. BP Batam acts as the central authority in regulating and supervising the granting of land management rights to new rights holders, ensuring that the process is carried out in accordance with applicable rules and regulations. The exercise of authority by the Batam Concession Agency (BP) in issuing land management rights for new rights holders is a concrete effort to realize legal certainty in the Batam area. Through its authority, BP Batam ensures that every grant of land management rights is carried out based on the principles of transparency, and accountability, and in accordance with applicable regulations. It is important to ensure that new rights holders get their rights clearly and without ambiguity, so as to encourage investment and sustainable development in Batam. Exercising its authority over the issuance of land management rights, BP Batam faces a number of obstacles, including complicated bureaucracy, potential discrepancies between central and regional regulations, and inadequacy of competent human resources. These obstacles have the potential to hinder the achievement of legal certainty for new rights holders. To overcome this, intensification efforts are needed in bureaucratic reform, harmonization of regulations, and capacity building and training for BP Batam apparatus. With this solution, it is hoped that the process of issuing land management rights can run more efficiently, and transparently, and provide legal certainty expected by rights holders and investors in Batam. It is recommended that the central and local governments to continue to support BP Batam with policies that facilitate the procedure for issuing land management rights. BP Batam should develop a digital system for the issuance of land management rights that can simplify the process, increase transparency, and strengthen legal certainty for new rights holders. To establish a regular dialogue forum between BP Batam, new rights holders, and other relevant parties to identify and resolve obstacles that arise in real time.